Evaluation of primary production in the estuaries of the Razdolnaya/Suifen and Sukhodol Rivers (Peter the Great Bay, Japan Sea) - Anna S. Vazhova; Yury I. Zuenko (Известия ТИНРО)
Production-destruction balance is determined and primary production is evaluated for different parts of the estuaries of two rivers with different hydrological regime in Peter the Great Bay basin (Razdolnaya/Suifen and Sukhodol) in different seasons on the data of chemical surveys conducted in 2010-2013. The values of production and destruction are calculated from the difference between observed nutrients (phosphorus) concentration in the estuaries and their potential concentration conditioned by the river water dilution. The nutrients concentration in the water passing through estuaries increased in their upper parts over the potential values due to the nutrients influx from destruction, then decreased below the potential values because of the consumption for photosynthesis. Production processes prevailed over the estuaries in spring, the sign of production-destruction balance changed in summer from destruction in the upper estuaries to production in the lower estuaries, and destruction processes prevailed in autumn-winter. Productivity of the Razdolnaya/Suifen estuary is based mainly on utilization of terrigenous nutrients dissolved in its highly mineralized water, but in the Sukhodol estuary the nutrients of terrigenous origin are consumed quickly and its productivity is maintained by recycling of nutrients. Passing the estuaries, 1 m3 of both rivers water produces on average 0.8-1.0 gС/m3km that corresponds to values of primary production up to 5.6 gC/m3day in summer, with the maximum in the upper parts of the external estuaries under salinity 5-10 ‰, at the haline front dividing almost fresh water of the internal estuary from brackish water of the external estuary. Taking destruction of organic matter into account, net production is mostly below zero in the river parts of estuaries, particularly in autumn, it reaches the maximum in the upper part of external estuaries (up to 0.7-1.0 gC/m3km or 3-5 gC/m3day) and remains on lower but positive level further offshore. So, estuaries are simultaneously «marginal filters» limiting penetration of terrigenous nutrients into the sea and «factories of nutrients»: the latter process dominates in their internal parts and enhances considerably biological productivity of these water bodies.